Hemorrhagic cystitis induced by intravenous esketamine in the treatment of new-onset refractory status epilepticus in children: a case report - Ding, Jin-Meng; Miao, Hong-Jun; Liu, Yao (Frontiers in Pediatrics, 2025)
IntroductionEsketamine, the S-enantiomer of ketamine, has been considered for terminating new-onset refractory status epilepticus (NORSE). However, there is limited large-scale data on its safety and comparative effectiveness. Ketamine-associated cystitis (KAC) is a known complication of chronic recreational ketamine use; however, there are few reports of cystitis caused by intravenous esketamine in children.MethodsWe report a 9-year-old boy diagnosed with NORSE, who was treated with esketamine as an anesthetic to terminate status epilepticus. He received a continuous intravenous infusion of esketamine, starting at 2 mg/kg/h and gradually increasing to a maximum of 5 mg/kg/h. The dose was reduced starting on day 9 with no apparent convulsive seizure. On day 13, he developed fluid imbalance, and an ultrasound revealed bladder wall thickening. By day 16, he exhibited gross hematuria.ResultsAccording to the Naranjo adverse reaction probability scale, esketamine was the possible cause of the Adverse Drug Reaction (ADR). After stopping esketamine and initiating urine alkalinization with sodium bicarbonate, his urinalysis and sedimentation rate normalized.DiscussionHemorrhagic cystitis may occur during continuous high-dose intravenous esketamine infusions. Early multidisciplinary monitoring of lower urinary tract symptoms and implementation of preventive measures in pediatric patients is essential to avoid serious urinary tract complications.